Oxime and atropine failure to prevent intermediate syndrome development in acute organophosphate poisoning - Vučinić, Slavica; Antonijević, Biljana; Ilić, Nela; Ilić, Tihomir (Vojnosanitetski pregled, 2017)
Introduction. Intermediate syndrome (IMS) was described a few decades ago, however, there is still a controversy regarding its exact etiology, risk factors, diagnostic parameters and required therapy. Considering that acute poisonings are treated in different types of medical institutions this serious complication of organophosphate insecticide (OPI) poisoning is frequently overlooked. The aim of this paper was to present a case of IMS in organophosphate poisoning, which, we believe, provides additional data on the use of oxime or atropine. Case report. After a well-resolved cholinergic crisis, the patient developed clinical presentation of IMS within the first 72 h from deliberate malathion ingestion. The signs of IMS were weakness of proximal limb muscles and muscles innervated by motor cranial nerves, followed by the weakness of respiratory muscles and serious respiratory insufficiency. Malathion and its active metabolite were confirmed by analytical procedure (liquid chromatography-mass spectrometry). Pralidoxime methylsulphate, adiministered as a continuous infusion until day 8 (total dose 38.4 g), and atropine until the day 10 (total dose 922 mg) did not prevent the development of IMS, hence the mechanical ventilation that was stopped after 27 h had to be continued until the day 10. Conclusion. Continuous pralidoxime methylsulphate infusion with atropine did not prevent the development of IMS, most likely due to the delayed treatment and insufficient oxime dose but also because of chemical structure and lipophilicity of ingested OPI. A prolonged intensive care monitoring and respiratory care are the key management for the intermediate syndrome.